Boosting Junior High School Students’ Vocabulary Skills through Educational Tiktok Content - Setyaningrum, Riya Risqi; Faridah, Fita; Luthfiyati, Dian; Fitriana, Maslakhatul (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2026)
This study aims to investigate the effectiveness of using TikTok as a medium to enhance students' vocabulary mastery. Employing a quantitative approach with a quasi-experimental design, the research was conducted at SMPN 3 Lamongan. The study involved class 7D as the experimental group (n=30) and class 7G as the control group (n=30). Data were collected through multiple-choice vocabulary tests administered as pre-tests and post-tests to assess students' vocabulary knowledge before and after the treatment. The experimental group received vocabulary instruction integrated with TikTok content, while the control group followed conventional teaching methods. Statistical analyses, including normality testing, the Wilcoxon signed-rank test, and the Mann–Whitney U test, were performed using SPSS version 25. The Mann–Whitney U test yielded a significant value for Asymp. Sig. (2-tailed) = 0.000, which is lower than the threshold of 0.05, indicating a statistically significant difference between the two groups. These findings support the research hypothesis and demonstrate that incorporating TikTok into the vocabulary learning process significantly impacts students' vocabulary acquisition. The results suggest that social media platforms like TikTok can be effectively utilized as complementary tools in English language learning. This medium also enhances students’ motivation, learning engagement, and interest in participating in English learning. Furthermore, the findings of this study make a meaningful contribution to the field of English education by demonstrating that the integration of short-video-based social media platforms such as TikTok can serve as an effective and innovative instructional strategy for improving students’ vocabulary mastery and their engagement in the learning process.